Ground penetrating radar data from beaver ponds in Alaska tundra, August 2024 ... - Correa Rangel, Rodrigo; Glass, Thomas; Tape, Ken (Arctic Data Center, 2024)
In recent decades, beavers have extended their range from the boreal forest into the Arctic tundra, altering tundra streams and surrounding permafrost at local to regional scales. In lower latitudes, beaver damming can convert streams, backwaters, and lake outlets into connected ponds, which in turn can change the course of channels, temperature of streams, sediment loads, energy exchange, aquatic habitat diversity and nutrient cycling, and riparian vegetation. In the Arctic, effects of beavers may include enhanced thawing of permafrost, increased stream temperatures, and changes in seasonal ice in streams, as well as complex ecosystem responses. This study will 1) document movement of beavers from the forest into tundra regions, 2) understand how stream engineering wrought by beavers will change the arctic tundra landscape and streams, and 3) predict how beavers will expand into tundra regions and alter stream and adjacent ecosystems. Results will be of interest to local communities and resource managers, ...